Studies of Some Co(II), Ni(II) and Cu(II) Complexes with a Mixed Ligand Schiff Base - RAI, B.K.; SHARMA, KAUSHLENDRA (Asian Journal of Chemistry, 2010)
Synthesis of mixed ligand Schiff base complexes of general formula of the type [M(DOSC)2X2], were M = Co(II), Ni(II) and Cu(II), DOSC = 1,2-dimethyl-4-oxoquinazoline semicarbazone and X = Cl–, Br–, I–, NO3– and ClO4–. These complexes were characterized by elemental analysis, molar conductance, IR spectra, electronic spectra and magnetic susceptibility. On the basis of above observations the ligand DOSC have been proposed to act in a bidentate manner, coordinating to the metal ion through the nitrogen and oxygen atom of semicarbazone moiety. The remaining coordination sites are occupied by anions such as Cl–, Br–, I–, NO3– and ClO4–. Electronic spectra and magnetic susceptibility measurements reveal octahedral geometry around the central metal ion. The complexes were found to be non-electrolytic in nature on the basis of low value of molar conductance.